Transformasi Pendidikan: Memperkuat Kecerdasan Sosial dan Emosional Anak di Era Disrupsi - Cannavaro, Juliano; Asbari, Masduki; Nurmayanti, Rini (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to explore the extent to which the world of education has been transformed due to the impact of COVID-19. It can be seen the importance of developing social and emotional intelligence in children through social interaction and play-centered learning, in this context emphasizing the need to consider learning methods. Encourage analysis and creativity, not just memorization. The research methods used in this transcript are descriptive and narrative approaches that highlight the importance of social interaction, play, and sensory and motor development in children's learning processes. The source of the data obtained listened to an oral narrative from a Youtube channel entitled